Unlocking digital super powers: Being responsive to change is now par for the course within industry, but how can digital transformation be accelerated? - Awad, Mohamad (MEED Business Review, 2019)
There is a massive opportunity for digitisation in industrial sectors such as oil and gas Tools to monitor, interpret and analyse data in real-time are key Predictability and transparency are the core requirements for regional industry Using machine learning to predict downtime is leading digital transformation in the global downstream industry Q. Why is digital transformation so important for industrial customers? Based on first principle simulation, process optimisation modelling allows businesses to anticipate opportunities and be nimble enough to leverage opportunities for profit - whether through anticipatory procurement, predictive maintenance or evaluating process changes before they are deployed. Industry 4.0 has captured imaginations because of its possibilities, but technologies such as loT, artificial intelligence and machine learning also require domain expertise and case specific innovations to be optimal.